Activity engagement and physical function in old age sample. (March 2017) - Shah, Krupa N.; Lin, Feng V.; Yu, Fang; McMahon, James M.
Highlights: We evaluated the relationship of engagement in individual and combined physical activity, mental activity, and social activity and physical function. Combined physical and mental activity engagement was associated with better physical function, especially in gait speed. Future interventional research should investigate the combination of both physical and cognitive training to prevent decline of physical function in older adults. Abstract: Objectives: To describe the patterns of engagement in mental, physical, and social activity (MA, PA, and SA) and to examine the relationship between combined activity engagement and physical function among community-dwelling older adults. Design: Cross-sectional correlational study. Setting: Multiple communities. Participants: A total of 466 individuals aged 55 years or older. Measurements: Physical function was assessed using grip strength and gait speed. Engagement in PA, MA and SA was obtained from self-report questionnaires. Results: We identified four classes ("Active PA and MA", "Active MA", "Active PA", and "Inactive") that significantly differed in the frequency of engagement in MA and PA using latent class analysis. SA didn't differ across classes. Controlling for age, the "Active PA and MA", "Active MA", "Active PA" groups displayed similar grip strength that was superior to the "Inactive" group. "Active PA and MA" group had best gait speed relative to other groups, especially "Active MA" and "Inactive" group, while the "Active PA", "Active MA", and "Inactive" group were similar in gait speed. Conclusion: Combined physical and mental activity engagement was associated with better physical function, especially in gait speed. Future interventional research should investigate the combination of both physical and cognitive training to prevent decline of physical function in older adults.